Cleome viscosa: successful cultivation in tarai region, Uttarakhand - Prakash, Om; Ballabh, Basant; Agarwal, Ankur (Indian Farming, 2018)
Herbal medicine plays an important role in the health care system of human beings since ancient times. About one-fourth of prescribed drugs are estimated to contain extracts or active ingredients of plant origin. This article provides the information of the plant Cleome viscosa from Uttarakhand region of India. Cleome viscosa is used for its nutritional, antioxidant and free radical scavenging properties which is also used to treat many diseases in different traditional systems of medicine all over the world. In India Cleome viscosa is used to treat epilepsy, irritable bowel syndrome and protozoal and worm infections.